Antioxidant and Anti-aging Activity of Ziziphus jujuba Extract - Xiaonan YE; Huihui ZENG; Siqi LIU; Yixiang LI; Lili HUANG; Shuang YU; Tingli LI; Yanyan WANG (Shipin gongye ke-ji, 2022)
Objective:To illustrate the antioxidant and anti-aging activity of Ziziphus jujuba extract in vivo and in vitro. Methods: The antioxidant activity of Ziziphus jujuba extract (0.05、0.10、0.20、0.40、0.60、0.80、1.00 mg/mL) was determined by DPPH free radical scavenging rate, ·OH radical clearance rate and Fe3+ reducing antioxidant power assayed in vitro. Three different doses of Ziziphus jujuba extract (0.1%、0.5%、1.0%) were given to the Drosophila melanogaster through the culture to study the in vivo antioxidant and anti-aging activity by testing the lifespans, negative geotaxis ability, SOD activity, MAD content and CAT activity. Results: The results of in vitro antioxidant activity showed that the Ziziphus jujuba extract could scavenge DPPH and OH free radicals in vitro, and its IC50 were 0.44 and 1.40 mg/mL, respectively. It also could reduce iron in vitro. The in vivo antioxidant and anti-aging activity results showed that the average life span of female and male D. melanogasterwere prolonged by 9.61% and 13.91% in 1.0% Ziziphus jujuba extract group compared with the control group (P<0.01). Also Ziziphus jujuba extract treatment improved the negative geotaxis ability in older female and male D. melanogaster (P<0.05 or P<0.01), decreased the MAD content (P<0.05 or P<0.01) and increased the SOD and CAT activity (P<0.05 or P<0.01). Conclusion: The Ziziphus jujuba extract has good antioxidant and anti-aging capacity in vivo and in vitro.